Mechanical properties and microstructure of Li2O-SiO2-P2O5-Al2O3-K2O-CaO glass-ceramics - Manlika Kamnoy (2018)
© 2018 Trans Tech Publications, Switzerland. In this study, the mechanical properties and microstructure of lithium disilicate glass–ceramics in the Li2O-SiO2-P2O5-Al2O3-K2O-CaO glass system were investigated. The glass-ceramics were prepared from the glass melt by casting into mold on hotplate. After that the glass was heat treated at 650-800 °C for 2 h. The heat treatment temperatures were determined from the differential thermal analysis (DTA). The phase formation and microstructure of the glass–ceramics were characterized by X-ray diffraction (XRD) technique and the scanning electron microscopy (SEM). Moreover, the mechanical properties was investigated by Vickers hardness testing. The results indicated that the samples confirmed the occurrence of Li2SiO3, Li2Si2O5, Li3PO4, and LiAlSi2O6phases in the prepared glass ceramics. The optimum heat treatment temperature results in the physical properties with a high Vickers hardness values in the range of 5.4-5.8 GPa.